Auto-dial security system to brigade station (fire detection) / Hafsah Jaafar - Jaafar, Hafsah (1998)
This thesis proposed the software development of the computer based controlled system which can transmit the message automatically when an emergency occurs (for example occurs in the building). The system will incorporate automatic dialing and message transmission. The present systems are not very useful in order to locate the specific place and to get immediate help. With the new system to be developed, the security system will be safe and number of manpower can be reduced significantly.